2022
DOI: 10.47391/jpma.3801
|View full text |Cite
|
Sign up to set email alerts
|

Cognition improvement strategies, study behaviors and stress among medical students of Dow University of Health Sciences: a cross-sectional study

Abstract: Objective: To determine the effects of cognition improvement strategies on academic performance, stress and sleep quality of medical students. Method: The cross-sectional study was conducted att he Dow University of Health Sciences, Karachi, from March 2019 to March 2020, and comprised medical students regardless of gender and academic year. Academic performance was assessed through grade point average, while stress and sleep were assessed using the Perceived Stress Scale and Pittsburgh Sleep Quality Index. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…Our survey revealed that 88.3% of medical students in three countries (Egypt, Jordan, and Sudan) had consumed at least one substance considered a CE during their studies. A similar prevalence of CE use (87.6%) was observed in Pakistan (24). Interestingly, our study showed that females consumed CE more often than men (60.8% vs. 39.2%) which aligns with another study conducted in Poland (10).…”
Section: Discussionsupporting
confidence: 91%
“…Our survey revealed that 88.3% of medical students in three countries (Egypt, Jordan, and Sudan) had consumed at least one substance considered a CE during their studies. A similar prevalence of CE use (87.6%) was observed in Pakistan (24). Interestingly, our study showed that females consumed CE more often than men (60.8% vs. 39.2%) which aligns with another study conducted in Poland (10).…”
Section: Discussionsupporting
confidence: 91%
“…Our survey revealed that 53% of medical and dentistry students used at least one substance considered as CEs during their studies. In other countries, the prevalence of CE use was lower, e.g., 32% in Portugal [ 18 ], and higher, e.g., 87.6% in Pakistan [ 10 ], than in our study. Even excluding from the consideration students using only caffeine, almost 42% of our respondents used at least one other CE.…”
Section: Discussioncontrasting
confidence: 80%
“…An important factor influencing the decision was knowing someone who had used these kinds of drugs [ 27 ]. Ashraf Jahangeer et al [ 10 ] noticed a similar tendency that men used the CEs more often than women, but differences were not so significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation